Income Tax Article 21 Receipt Before and After the Implementation of Tax Incentives for Permanent Employees During the Pandemic of Covid-19 - Intan Puspanita; Asih Machfuzhoh; Hulmah; Selly Anggraeni Haryono (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
The purpose of this Final Project Report research is to find out the Level of Article 21 Income Tax Acceptance Before and After the Existence of Tax Incentives for Permanent Employees During the Covid-19 Pandemic at the Cilegon Primary Tax Service Office. The method used is the descriptive method. Sources of data come from observations and interviews obtained from the Cilegon Primary Tax Service Office. The results of this study show that the level of income tax revenue under Article 21 after tax incentives, especially in 2020 and 2021, has decreased and has not even reached the target set. The Covid-19 pandemic has limited human activity which has had an impact on the decline in the economy in Indonesia, thus reducing revenue from Article 21 Income Tax. Efforts made by KPP Pratama Cilegon in increasing tax revenues include holding tax classes, conducting socialization, conducting counseling, and applying tax sanctions.